Identification and description of the antennal sensilla of Liogenys suturalis (Coleoptera: Scarabaeidae) - Menis,Flavio T. (2021)
ABSTRACT Species of the scarab beetle genus Liogenys are potential pests to several crops in Brazil. This study aimed to describe the antennal sensilla of Liogenys suturalis (Blanchard, 1851). Adults were collected in a pasture area in Bálsamo, São Paulo state, Brazil, using a light trap. The antennae were dissected and images of the antennal sensilla were obtained using a scanning electron microscope. Sensilla ampulacea (pores), s. auricilica, s. basiconica, s. placodea, and s. trichodea are present in the lamellae. The antenna of females have 4399 sensilla, of which 3671 (83.5%) are s. placodea, 422 (9.5%) s. coeloconica, and 306 (6.9%) s. auricilica. The antennae of males have 4039 sensilla, of which 3117 (77.1%) are s. placodea, 353 (8.7%) s. coeloconica, and 569 (14.1%) s. auricilica. The antennal sensilla of the genus Liogenys have been described for the first time.